Turkish internet users' awarness of and attitudes toward HIV/AIDS and other STDs - Celik, Mustafa (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2007)
Objective: The Internet is currently used as a tool to obtain information, make conversation, and find sexual partners. The aim of this study was to investigate Turkish Internet users' awareness of and attitudes toward HIV/AIDSand other sexually transmitted diseases (STDs) by using a standard web-based questionnaire. Method: Our study was performed using a standard web-based questionnaire form open to all Internet users consisting of questions and statements about HIV/AIDS and other STDs. The study included 898participants. Results: The most common sources from which respondents obtained STD-related information were stated as primarily print sources, followed by the Internet. Although men and women had similar educational levels, women were more informed about HIV/AIDS (p = 0.001). People with better awareness of HIV/AIDS had more information and also had different attitudes (p = 0.001). Conclusion: Our study shows that Turkish Internet userslack HIV/AIDS and other STD- related awareness and have mistaken opinions. Because it is the best and the fastest communication tool of our age, the Internet should have correct orientations and should be developed in order to give people access to reliable information. Because young people increasingly use the Internet on a daily basis, this medium might be a good educational tool for HIV/AIDS and other STDs.
Keywords: AIDS; Computer Communication Networks; Health Education; HIV; MESH/slv; Računalniške mreže; Sexually Transmitted Diseases; Spolno prenosljive bolezni; Turčija; Turkey; Zdravstvena vzgoja